La seguridad alimentaria y el comercio agroalimentario en América Latina y el Caribe - Food and Agriculture Organization of the United Nations; International Food Policy Research Institute; Piñeiro, Valeria; Illescas, Nelson; Rodriguez, Augustín Tejeda; McNamara, Brian (Food and Agriculture Organization of the United Nations, 2023)
Synopsis: Latin America and the Caribbean is the world's largest net exporting region for agrifood products, yet the region faces immediate challenges to food security. Increasing intraregional trade presents an opportunity to eradicate hunger in the region. This brief provides a synopsis of key findings from a recent FAO-IFPRI report, La Seguridad Alimentaria y el Comercio Agroalimentario en América Latina y el Caribe (Food Security and Agrifood Trade in Latin America and the Caribbean), which examines the potential for expanding intraregional trade in LAC, and offers recommendations on the way forward.